Alternative dissertation formats in education-based doctorates. Issue 3 (16th April 2022) - Anderson, Tim; Saunders, Gillian; Alexander, Ian
ABSTRACT: The doctorate and doctoral writing remain popular areas of inquiry and discussion, and yet very little research has empirically investigated the trends in dissertation types and how these trends might indicate broader changes in dissertation writing practices. This article builds on our recent work that investigated the macrostructures and research designs of 1, 373 education-based PhD dissertations from five major Canadian research universities. In this current article, we more deeply explore the emergence in popularity of two 'alternative' or non-traditional dissertation macrostructures in education fields: the manuscript-style dissertation and the topic-based PhD dissertation. We highlight the popularity of these two dissertation types as evidence of shifting notions of what doctoral research and dissertations can (and do) look like in contemporary PhD programs. We focus specifically on these two dissertation macrostructures that were prevalent in our analysis, yet which are scarcely addressed in education-based dissertation resources. We provide a deeper reflection on the popularity of these dissertation models from our large-scale study, the ways these types of dissertations are organized at the global (macrostructural) level, and the chosen research designs, number of chapters, word counts, and authorship status (as either single-authored, partially co-authored, or mostly co-authored texts).